Production of interferon gamma, interleukin 2, interleukin 4, and interleukin 10 by CD4+ lymphocytes in vivo during healing and progressive murine leishmaniasis. - Heinzel, F P (1991)
The expression of interleukin (IL) 2, IL-4, IL-10, and interferon gamma (IFN-gamma) by lymphocyte subsets was examined during infection of resistant C57BL/6 and susceptible BALB/c mice with the protozoan parasite Leishmania major. CD4+ and CD8+ T lymphocytes and B lymphocytes were isolated from the lymph nodes draining infectious lesions, and their RNA was examined for lymphokine transcripts. Distinct patterns of CD4+ cell cytokine expression were apparent: C57BL/6 CD4+ cells contained IFN-gamma and IL-2 mRNA, whereas BALB/c CD4+ cells expressed IL-4 and IL-10 message. CD8+ cells contributed little lymphokine expression during disease, but B cells were a major source of IL-2 mRNA in both strains of mice. BALB/c mice made resistant by treatment with anti-CD4 antibody at the time of infection repopulated lymph nodes with CD4+ cells that expressed IL-2 and IFN-gamma. Protective treatment with anti-IL-4 antibody in vivo also resulted in the appearance of CD4+ cells with increased IFN-gamma and diminished IL-4 and IL-10 expression. These data establish CD4+ cells as the primary source of IFN-gamma in healing mice and of IL-4 and IL-10 during progressive infection and confirm that the spectral extremes of this disease are characterized by the presence of CD4+ cells expressing Th1 or Th2 phenotypes in vivo.